Aktivitas Antioksidan Sirup Kombinasi Ekstrak KulitManggis Dan Daun Sirsak Dengan Penambahan VariasiKonsentrasi Gula Pasir - Larasati, Ika, Dra. Aminah Asngad, M.Si (2015)
Mangosteen rind is a waste of mangosteen fruit during this utilization is still in the form of product diversification.. In a study mangosteen rind contains xanthones, mangostin which is a new type of histamine, but it also has antiinflammatory activity of mangosteen peel and antioxidants.. Other plants that can be used as a source of antioxidants is soursop with soursop leaf content were found to contain saponins, tannins, flavonoids, and glycosides. In this study aims to determine the antioxidant activity, oragonoleptik testing and acceptance of society towards syrup combination of mangosteen peel extract and soursop leaves.. The study design using the experimental method with completely randomized factorial design that is a factor of 1 combination of mangosteen peel extract and extract of soursop leaf with F1 ratio: 75%: 25%, F2: 50%: 50% and F3: 25%: 75%. Factor 2 is the concentration of sugar that is G1: sugar concentration of 80%, G2: 90% sugar concentration. From the research that has been conducted on the highest antioxidant activity assay F2G1 treatment is 71.76%. In F1G1 treatment is the most preferred treatment Mindless panelists have attractive color, sweet taste and not air scent of rotten with mangosteen skin ratio and soursop leaves 75: 25% and variations in sugar concentration of 80%. From this research proves the effect of sugar concentration of the syrup of antioxidant activity, organoleptic and acceptance in the community.